Enhancing literacy through picture-word interventions: a mixed methods study on English learners in southwestern Kansas - Struzik, Eugene V., III (My University, 2025)
This quasi-experimental study examined the effectiveness of the Picture Word Induction Model (PWIM) on vocabulary, comprehension, and literacy attitudes among fifth-grade English Learners at Sunrise Elementary School, a pseudonym for a rural school in southwest Kansas. Employing a convergent parallel mixed methods design, the study integrated quantitative assessments and qualitative interviews to provide a comprehensive evaluation of PWIM’s influence on literacy outcomes, attitudes, and engagement. The study included 44 fifth-grade English Learners who participated in an eight-week PWIM intervention. Quantitative data were collected using FastBridge assessments and the Garfield Reading Attitude Survey. The Garfield data revealed statistically significant gains in both recreational (z = 4.04, p < .001) and academic (z = 3.62, p < .001) reading attitudes, while FastBridge results showed descriptive improvements in vocabulary and comprehension that were not statistically significant within the study’s timeframe. The qualitative strand consisted of semi-structured interviews with 17 focal participants. Analysis indicated that students developed greater confidence in reading aloud, shifting from fear and avoidance to increased willingness to volunteer and persist when encountering unfamiliar words. PWIM also reduced resistance to writing tasks by providing scaffolded vocabulary entry points, encouraged reading habits beyond school, and supported higher engagement and enjoyment of literacy activities. Taken together, these findings suggest that PWIM contributed meaningfully to attitudinal and confidence growth, creating more positive literacy identities for English Learners, even though measurable achievement effects were not yet statistically significant. The study highlights the potential of PWIM as a visually scaffolded and student-centered instructional model that can foster both affective and behavioral shifts in literacy, with implications for future research and classroom practice in linguistically diverse settings.
Keywords: Picture; Word; Induction; Model; Reading; Intervention